Kuwait : Report on Observance of Standards and Codes: FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
This study provides a summary of the Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT) measures in Kuwait and the level of compliance with FATF recommendations, and contains how the AML/CFT system could be strengthened. A detailed assessment report (DAR) is prepared. The DAR was adopted by the Middle East and North Africa Financial Action Task Force (MENAFATF). The preventive measures adopted in financial institutions are explained. The National AML/CFT committee and the committee on Combating Terrorism (CCT) are outlined. Various preventive measures are also ascribed in this paper.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet